Seven ways of looking at Fan Fiction - Parker, Ruby (WritingThreeSixty: Journal or Research and Creative Text, 2019)
This essay examines the phenomenon of fan fiction from different angles, from the point of view of the readers and writers, to the attitude of the literary establishment and my own personal experi-ence as a member of the Harry Potter fandom. The purpose is to show the cultural significance and merits of this overlooked genre, which has grown exponentially in a post-internet, post-Potter world. This is done by examining its influence on a new generation of writers like Cassandra Clare, who got their start on platforms such as fanfiction.net and have since achieved great commercial success in publishing. It attempts to explain the popularity of the genre, by looking at how it functions as a „shadow world‟ to established works of fiction like Twilight, allowing fan communities to take collective ownership of texts and create multiple interpretations. Many creators like Robin Hobb and Diana Gabaldon are threatened by this change in ownership – and accusations of plagiarism are often leveraged to retain control. However, the essay argues that the majority of fan fiction is not written to profit from another‟s creation, but out of genuine love for it. Its popularity with young adults in particular has also made fan fiction an alternative tool of sexual education that allows marginalised individuals like members of the LGBTQI community to find representation, by writing themselves into popular narratives.